Pengembangan Aplikasi SANTRI PTSL Untuk Percepatan Pengumpulan Data Yuridis di Kantor Pertanahan Kabupaten Kampar - Mhd Teguh Saputra; I Gusti Nyoman Guntur; Slamet Wiyono (Sekolah Tinggi Pertanahan Nasional, 2021)
The purpose of this research is to find out how the SANTRI PTSL application can accelerate the juridical data collection and the feasibility of developing the SANTRI PTSL application. Using qualitative methods with a descriptive approach and data collection techniques by means of observation, interviews and questionnaires. SANTRI PTSL is an application that helps the work of the juridical task force. The output of the SANTRI PTSL application is a form of application for land registration that has been filled in automatically following the data submitted by the community to the officers. After training and simulating the use of the SANTRI PTSL application for juridical data collection officers, it is seen that this application is able to accelerate the collection and processing of juridical data, and in terms of the feasibility of developing this application it is also suitable for use in the Kampar Land Office after the feasibility test and simplification of the application forms according to the format used by the Land Office. By using the SANTRI PTSL application, the Kampar Land Office can optimize existing human resources and save time in completing PTSL activities. Inovasi pertanahan guna mendukung percepatan kinerja dan pelayanan pertanahan terus diupayakan. Penelitian ini bertujuan untuk mengetahui bagaimana aplikasi SANTRI PTSL dalam mempercepat pengumpulan data yuridis dan kelayakan pengembangan aplikasi SANTRI PTSL. Metode penelitian dilakukan secara kualitatif deskriptif, pengumpulan data dengan cara observasi dan wawancara.Hasil kajian menunjukkan bahwa aplikasi SANTRI PTSL yang diimplementasikan dapat mengoptimalkan SDM yang ada dan menghemat waktu dalam penyelesaian kegiatan PTSL. Aplikasi ini layak digunakan setelah dilakukanya pengembangan dan penyederhanaan blanko permohonan disesuaikan dengan standar yang ada pada Kantor Pertanahan Kabupaten Kampar. Aplikasi ini juga mampu mengintegrasikan data fisik dan data yuridis untuk mempermudah pengadministrasian pertanahan pada Kantor Pertanahan Kabupaten Kampar.Kata kunci: Pendaftaran Tanah, Inovasi, SANTRI PTSL